EFL Students’ Needs and Achievement: A Study at an Islamic University in Jambi - Shynta Amalia; Wahyuni Fitria; Muhammad Iqbal Ramdhani; Hilma Suryani (Ta'dib: Jurnal Pendidikan Islam, 2021)
This study aims to respond the regulation of teaching and learning English in higher education. Since there is no clear regulation of what supposed to be taught, some institutions decide different requirement for the teaching and learning English. This study focused on analyzing and evaluating the students’ actual needs in learning English. A quantitative study was conducted toward 113 non-English department students who have taken English subject in an Islamic University in Jambi. This study explored both of the students’ actual needs and experiences of their learning English in the classroom. The results indicate that having the four skills as a part of teaching and learning English in the classroom is important for the students. The students also mentioned that completing their study is not the only reason to learn English. They believe that learning English is a golden key to be a part of world class community. In spite of mastering reading as the main focus of learning process, the students still face difficulties in understanding the ideas in English since they have limited vocabulary and grammar. They also stated that it is hard for them to get the meaning of what they read because they do not know how the sentences are put together. As the results, it is suggested that the process of teaching and learning English must be revisited